2001
DOI: 10.1007/s002320010045
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and Function of the Rat Colonic Epithelial K + Channel K V LQT1

Abstract: KVLQT1 (KCNQ1) is a voltage-gated K+ channel essential for repolarization of the heart action potential that is defective in cardiac arrhythmia. The channel is inhibited by the chromanol 293B, a compound that blocks cAMP-dependent electrolyte secretion in rat and human colon, therefore suggesting expression of a similar type of K+ channel in the colonic epithelium. We now report cloning and expression of KVLQT1 from rat colon. Overlapping clones identified by cDNA-library screening were combined to a full leng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
62
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(67 citation statements)
references
References 30 publications
4
62
0
Order By: Relevance
“…cDNAs were amplified with Taq polymerase (Invitrogen), using specific primers designed from sequences of the following cloned K ϩ channels: rat KvLQT1 (Ref. 27, GenBank Accession No. AJ133685), Slo1 (GenBank Accession No.…”
Section: Molecular Biologymentioning
confidence: 99%
“…cDNAs were amplified with Taq polymerase (Invitrogen), using specific primers designed from sequences of the following cloned K ϩ channels: rat KvLQT1 (Ref. 27, GenBank Accession No. AJ133685), Slo1 (GenBank Accession No.…”
Section: Molecular Biologymentioning
confidence: 99%
“…In rat distal colon the basolateral K ϩ conductance is formed by at least two different types of K ϩ channels, activated by Ca 2ϩ or cAMP-dependent agonists (8). Electrophysiological studies in these cells have revealed the candidate K ϩ channel involved in Cl Ϫ secretion to be KCNQ1, a low conductance (1-3 pS) K ϩ channel, which is activated during cAMP-stimulated Cl Ϫ secretion (9). Other types of K ϩ channels have also been implicated in chloride secretion, including the Ca 2ϩ -dependent KCNN4 channel (10).…”
mentioning
confidence: 99%
“…The rat KCNQ1 channel was cloned from colonic tissue and expression was demonstrated in both the crypt and surface cells (9). KCNQ1 is a voltage-gated channel, which plays a crucial role in controlling salt and water homeostasis in a number of epithelia (11).…”
mentioning
confidence: 99%
“…In order to maintain the membrane potential at rest and during Cl -secretion, K + must be recycled out of the cell across the basolateral membrane [3]. In rat distal colonic epithelia, which is a widely used animal model for the study of intestinal Cl -secretion, the basolateral K + conductance is formed by at least two different types of K + channels, one activated by Ca 2+ -mobilizing secretagogues and the other by cAMP-dependent agonists [4,5]. Several studies have revealed the latter to be KCNQ1, a low-conductance (1-3 pS) basolateral K + channel which is activated during cAMP-stimulated Cl -secretion and inhibited by chromanol 293B and HMR-1556 [6,7].…”
Section: Introductionmentioning
confidence: 99%